Sugarcane Bagasse-Derived Activated Carbon- (AC-) Epoxy Vitrimer Biocomposite: Thermomechanical and Self-Healing Performance - Balaji Krishnakumar; Debajyoti Bose; Manjeet Singh; R. V. Siva Prasanna Sanka; Velidi V. S. S. Gurunadh; Shailey Singhal; Vijay Parthasarthy; Liberata Guadagno; Poornima Vijayan P; Sabu Thomas; Sravendra Rana (International Journal of Polymer Science)
Vitrimeric materials have emerged as fascinating and sustainable materials owing to their malleability, reprocessability, and recyclability. Sustainable vitrimeric materials can be prepared by reinforcing polymeric matrix with bioderived fillers. In the current work, a sustainable vitrimer is prepared by incorporating biomass-derived activated carbon (AC) filler into the epoxy matrix to achieve enhanced thermal and mechanical properties. Thus, prepared biocomposite vitrimers demonstrate a lower-temperature self-healing (70°C for 5 min) via disulfide exchanges, compared to the pristine epoxy vitrimers (80°C for 5 min). Significantly, the self-healing performances have been studied extensively with the flexural studies; and changes in material healing efficiency have been demonstrated based on the observed changes in modulus.